Model of Socio-Psychological Diagnosis and Correction of Suicidal Behavior in Adolescents - Khaydarov Ismoil Olloqulovich (Genius Journals, 2023)
This article dealt with the human psyche, his inner world and the most intimate, personal aspects of this world, emotional shock, the situation of suicide, which is one of the situations of emotional distress. Although it is very unpleasant, but the suicide that occurs in life, that is, the suicide of people, is the most fragile, the most subtle mental state that can be observed in a person's life. The history of the manifestation of this state goes back to the distant past of mankind. The history of the problem of suicide is as old as the history of mankind and its psyche
Keywords: human psyche; world; emotional shock